A green fullerene: Synthesis and electrochemistry of a Diels-Alder adduct of [60]fullerene with a phthalocyanine - Linßen, Torsten; Dürr, Kai; Hanack, Michael; Hirsch, Andreas (Journal of the Chemical Society - Series Chemical Communications, 1995)
Spectroelectrochemical investigations of a Diels-Alder adduct of [60]fullerene with a nickel phthalocyanine show multiple reductions of both covalently bound electroactive moieties as well as characteristic changes of the optical phthalocyanine properties caused by the reduced fullerene.